Boys Together; Contemporary Approaches to Moral Education; and Foundations of Moral Education - Susan Day Harmison; Thomas D. Watts (Educational Considerations, 1987)
Three books reviews: Boys Together: English Public Schools, 1800 -1864, by John Chandos; Contemporary Approaches to Moral Education: An Annotated Bibliography and Guide to Research, by James S. Leming; and Foundations of Moral Education: An Annotated Bibliography, by James S. Leming.